A Highly Energetic N‐Rich Metal–Organic Framework as a New High‐Energy‐Density Material. Issue 3 (10th December 2015) - Zhang , Huabin; Zhang , Mingjian; Lin , Ping; Malgras, Victor; Tang , Jing; Alshehri, Saad M.; Yamauchi , Yusuke; Du, Shaowu; Zhang, Jian
Abstract: Metal–organic framework (MOF)‐based energetic material [Cu3 (MA)2 (N3 )3 ] (1 ; MA=melamine) was synthesized and structurally characterized (47.55 % N). The structural analysis revealed the existence of unusual multiwalled tubular channels and interweaving of single and double helical units in1 . The standard molar enthalpy of formation was found to be 1788.73 kJ mol −1, which is the highest value among previously reported MOF‐based energetic materials. The calculated detonation properties showed that1 can be used as a potential explosive. Sensitivity tests revealed that1 is insensitive and thus can function as a high‐energy‐density material with a favorable level of safety. Abstract : High‐energy MOF : The metal–organic framework [Cu3 (MA)2 (N3 )3 ] (MA=melamine) was synthesized hydrothermally as gray crystals (see figure). The structural analysis revealed the existence of unusual multiwalled tubular channels and interwoven single and double helices. Its standard molar enthalpy of formation of 1788.73 kJ mol −1 is the highest among previously reported MOF‐based energetic materials, and the calculated detonation properties showed that it can be used as a promising explosive.